Comment on “Relationship between Chinese Confucianism and modern Japanese language: taking I am a cat as an example” - Qing Wan (Trans/Form/Ação)
Commented article: GONG, M.; WANG, Y. Relationship between Chinese Confucianism and modern Japanese language: taking I am a cat as an example. Trans/Form/Ação: Unesp journal of philosophy Marília, SP, v. 47, n. 6, p. e02400297, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15880.